PRAKTIK JUAL BELI TANAMAN DENGAN SISTEM TAKSIRAN DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Sari, Nur Anggun; Bunyamin, Andi; Lawang, Hasanna; Bazith, Akhmad; Hasriani, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the practice of buying and selling patchouli plants using an estimation system in Ponggi Village, Porehu District, North Kolaka Regency, from the perspective of Sharia Economic Law. This study is a field research with a descriptive qualitative approach. Data were obtained through observation, interviews with farmers, contractors, and community leaders, as well as relevant documentation. Data analysis techniques were carried out through data reduction, data presentation, and systematic drawing of conclusions. The results of the study indicate that the negotiation process was carried out directly on the farmland with a bargaining mechanism until a mutual agreement was reached without any element of coercion, thus reflecting the principle of taradhi (mutual consent) as emphasized in the Qur'an Surah An-Nisa verse 29. Price determination was carried out based on an estimate of the condition of the plants before harvest and agreed upon in the form of a wholesale price. Although there is a potential difference between the estimated results and the actual harvest, the risk is borne by the contractor after the agreement is agreed. This practice is basically in line with the principles of fiqh muamalah which permits transactions as long as they do not contain elements of excessive gharar, tadlis, and injustice. Thus, the estimation system in the sale and purchase of patchouli in Ponggi Village can be considered valid according to Sharia Economic Law as long as it is carried out transparently, fairly, and based on the agreement of both parties.